Structural and functional abnormalities within sensori-motor and limbic networks underpin intermittent explosive symptoms in Tourette disorder. (June 2020) - Atkinson-Clement, Cyril; Sofia, Fuaad; Fernandez-Egea, Emilio; de Liege, Astrid; Beranger, Benoit; Klein, Yanica; Deniau, Emmanuelle; Roze, Emmanuel; Hartmann, Andreas; Worbe, Yulia
Abstract: Background: Intermittent explosive outbursts (IEO), manifesting as sudden episodes of verbal or physical aggression, are frequently present in patients with Tourette disorder (TD) and considered as one of the most disabling symptoms by patients and families. The neuronal correlates of these behaviours are poorly understood, and this was the primary objective of the present study. Methods: We assessed the presence of IEO in 55 patients with TD and then compared the subgroup of the patients with IEO to those without these manifestations using a multimodal neuroimaging approach. Results: 47% of TD patients presented IEO, which was frequently associated with attention deficit hyperactivity disorder (ADHD). TD patients (without ADHD) with IEO compared to TD without IEO, showed structural changes in the right supplementary motor area as well as in the right hippocampus (increased fractional anisotropy), and in the left orbitofrontal cortex (decreased mean diffusivity). Using these three nodes as seeds for resting state functional connectivity, we showed a lower connectivity within the sensori-motor cortico-basal ganglia network, and an altered connectivity pattern among the orbito-frontal cortex, amygdala and hippocampus. Conclusions: Overall, our results indicate that TD with IEO is associated with brain dysfunction related to a less efficient top-down control on action selection, and impairments related to emotional regulation, impulse control and aggressive behaviours.